Innate Lymphoid Cells in Crohn’s Disease - Wu, Ying; Shen, Jun (Frontiers in Immunology, 2020)
Innate lymphoid cells (ILCs) are a large family of cells of the immune system that performs various functions in immune defence, inflammation, and tissue remodelling.As a part of the innate immune system, ILCs are a distinct form of lymphocytes different from T and B cells. ILCs can provide host defense against the source of infection and initiate the repair and remodelling processes to restore and maintain host body homeostasis. The number of patients with Crohn's disease (CD) worldwide has continued to increase in recent years and this disease has brought sickness and death to many families. Numerous studies have found that ILCs contribute to ILCs also undergo a series of alternations during the development of CD and contribute to this disease. Despite this, the pathogenesis of CD is still not fully explained. So we keep researching and exploring. In this review, we have closely linked the latest progress on ILCs and CD, and introduced, in detail, the specific roles of four different types of ILCs in CD. We also describe new progress in the pathogenesis of CD, with particular emphasis on the plasticity of ILC3s in this disease. These new studies and findings may provide new insights and breakthrough points for the treatment of CD.